2014
DOI: 10.1016/j.cja.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency unsteadiness of vortex wakes over slender bodies at high angle of attack

Abstract: A type of flow unsteadiness with low frequencies and large amplitude was investigated experimentally for vortex wakes around an ogive-tangent cylinder. The experiments were carried out at angles of attack of 60-80°and subcritical Reynolds numbers of 0.6-1.8 · 10 5 . The reduced frequencies of the unsteadiness are between 0.038 and 0.072, much less than the frequency of Karman vortex shedding. The unsteady flow induces large fluctuations of sectional side forces. The results of pressure measurements and particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Strouhal numbers (St) of the sectional side-force at X/D = 2.5 were calculated and compared with published experimental data. 18 It can be seen that the St begins to agree with the experimental value as grid density excesses 4 × 10 6 . In the simulation, the 8, 234, 790 grid cells were used for formal computation.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Strouhal numbers (St) of the sectional side-force at X/D = 2.5 were calculated and compared with published experimental data. 18 It can be seen that the St begins to agree with the experimental value as grid density excesses 4 × 10 6 . In the simulation, the 8, 234, 790 grid cells were used for formal computation.…”
supporting
confidence: 58%
“…The results showed that the dominant frequencies of side-forces were far less than Kármán vortex shedding. Nevertheless, the experiment by Ma et al 18 cannot conclusively determine the sources of fluctuations of wall pressures and side-forces. Although Particle Image Velocimetry (PIV) was also used to reveal flow evolution, PIV is not time-resolved, so unable to identify frequencies of vortex fluctuations and to connect the fluctuations of side-forces to unsteadiness of vortices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the vortex shedding, however, other unsteady flow patterns also exist 15 . Degani et al 16 17 and numerical simulations 18 indicated that the forebody vortex pair is not stationary beyond 65 o AOA, but oscillates around a time-averaged asymmetric orientation with much lower frequencies than vortex shedding. Therefore, the leeward vortices around sharp-nosed slender bodies are essentially steady at most of the AOAs, including steady symmetric and asymmetric vortices, while large-scaled vortex motions exist only at sufficiently high AOAs (more than 65 o typically ).…”
Section: Introductionmentioning
confidence: 99%
“…However, theses techniques were not sufficiently effective. An extensive number of experimental studies were carried out in which the asymmetry was observed and studied [2,3,10,1,7,5,8,9,4,11] . However, to the authors' knowledge, all numerical investigations of asymmetric flow around slender bodies have introduced some form of perturbations into the flow field to induce asymmetry.…”
Section: Introductionmentioning
confidence: 99%